PENGGUNAAN METODE DISCOUNTED CASH FLOW DAN UKURAN NON KEUANGAN DALAM PENGANGGARAN MODAL: PENDEKATAN KONTINJENSI - Ahmad Rosyid (Jurnal Penelitian, 2011)
This study aims to (1) examine the degree of use between Discounted Cash Flow (DCF) method and non financial measures in capital budgeting (2) examine managers’ satisfaction on both methods when there is a contingency fit between those methods with two contingency variables: product standardization and firm strategy. This research used purposive sampling method to collect data. The research population was manufacturing firms listed in BEI and major non listed firms located in Jawa Tengah and got 35 responses. Multiple regression and Moderated Regression Analysis (MRA) were used to test the hypothesis. Research results indicate that (1) DCF method is not more important than non financial measures. Managers tend to use both methods simultaneously (2) firm strategy affects to DCF method and non financial measures significantly which it means that firms with prospector strategy tend to place more emphasis on non financial measures while firms with defender strategy tend to place more emphasis on DCF method. (3) product standardization has no effect on both methods (4) firm strategy has a moderating effect on the relation between two capital budgeting methods and manager’s satisfaction on budgeting process while product standardization has no effect.